2021
DOI: 10.1186/s13326-021-00235-3
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal temporal-clinical note network for mortality prediction

Abstract: Background Mortality prediction is an important task to achieve smart healthcare, especially for the management of intensive care unit. It can provide a reference for doctors to quickly predict the course of disease and customize early intervention programs for the patients in need. With the development of the electronic medical records, deep learning methods are introduced to deal with the prediction task. In the electronic medical records, clinical notes always contain rich and diverse medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The two representations were then concatenated to make the predictions. Concurrently to our work, Yang et al (2021) also showed the usefulness of combining time-series data with information from clinical notes. They used an LSTM model for the time-series part of the data and use a convolutional neural network with label-aware attention layer for the clinical notes.…”
Section: Related Worksupporting
confidence: 64%
“…The two representations were then concatenated to make the predictions. Concurrently to our work, Yang et al (2021) also showed the usefulness of combining time-series data with information from clinical notes. They used an LSTM model for the time-series part of the data and use a convolutional neural network with label-aware attention layer for the clinical notes.…”
Section: Related Worksupporting
confidence: 64%
“…Bayesian's methods are typically employed at this level 40 to support a voting process between the set of models into a global decision. Within late fusion there has been headway made to perform multitask deep learning [41][42][43][44][45][46][47] . A schematic for the 3 subtypes of data fusion is presented in Fig.…”
Section: Box 1 Terms and Conceptsmentioning
confidence: 99%
“…was taken by Tang et al who used three-dimensional CNNs and merged the layers in the last layer 113 . EHR and text data were fused together in 11 papers 41,44,80,107,109,116,122,126,134,136,142 . Of these, six 41,44,80,122,134,142 used long term short term (LSTM) networks, CNNs, or knowledge-guided CNNs 160 in their fusion of EHR and clinical notes.…”
Section: Intermediate Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several researchers have modeled both kinds of data for mortality prediction. For example, Yang et al (2021) proposed a multimodal deep neural network that considers both time series data and more clinical records. In addition, chronic and non-chronic patients are classified when dealing with clinical records.…”
Section: Introductionmentioning
confidence: 99%